Research on Recycled Plastic with Reinforced Kenaf for Automotive Application - A.S. Rahaida; Z.M. Haris; M.H.M.K. Hafizi; A.M.A. Firdaus; A. Firdaus; W.M. Uzir (Journal of the Society of Automotive Engineers Malaysia, 2025)
This study focuses on the development of rPET / rPP composite with a mixture of Kenaf and Sodium hydroxide (NaOH). The rPET sample preparation is from post-consumer waste. This involves a mixture of various compositions to obtain the best ratio for blending with Kenaf and 6% NaOH at 60°C for three hours. The mechanical properties of the mixture were studied using a tensile test. The distribution effect between rPET / rPP and kenaf mixture with NaOH has been studied under mechanical testing. All the materials will be placed into a blending machine to make sure all the materials are homogeneously mixed, depending on weight portions. The results showed there was an increase in the brittleness of composites when adding a higher percentage of kenaf.